Conceptual-Linguistic Superintelligence - Jilk, David J. (Informatica, 2017)
We argue that artificial intelligence capable of sustaining an uncontrolled intelligence explosion must have a conceptual-linguistic faculty with substantial functional similarity to the human faculty. We then argue for three subsidiary claims: first, that detecting the presence of such a faculty will be an important indicator of imminent superintelligence; second, that such a superintelligence will, in creating further increases in intelligence, both face and consider the same sorts of existential risks that humans face today; third, that such a superintelligence is likely to assess and question its own values, purposes, and drives.